A Study of Rural Teacher and Administrator Attitudes Toward Instructional Models for Educationally Handicapped Elementary Students - Wesley Little; Ace Cossart (Journal of Research in Rural Education, 1983)
The purpose of this study was to assess and compare the attitudes of special educators, regular educators, principals and special education directors regarding their models of instruction for the handicapped. This assessment and comparison was accomplished by surveying these four groups using a 35-item questionnaire. Bya random selection process, 738 questionnaires were distributed to the groups resulting in a 63070 rate of return. A five-point Likert scale was used to assess levels of satisfaction and differences tion directors). While there were statistically significant differences among the four groups on 8 of the 18 variables, the grand mean of responses on each question fell in or near the positive area on the Likert scale. Data revealed that these educators are reporting a high deree of satisfaction with present special education models